Late Split-Application with Reduced Nitrogen Fertilizer Increases Yield by Mediating Source–Sink Relations during the Grain Filling Stage in Summer Maize - Tao Deng; Jia-Hui Wang; Zhen Gao; Si Shen; Xiao-Gui Liang; Xue Zhao; Xian-Min Chen; Gong Wu; Xin Wang; Shun-Li Zhou (Plants, 2023)
In the North China Plain, the excessive application of nitrogen (N) fertilizer for ensuring high yield and a single application at sowing for simplifying management in farmer practice lead to low N use efficiency and environmental risk in maize (Zea mays L.) production. However, it is unclear whether and how late split application with a lower level of N fertilizer influences maize yield. To address this question, a two-year field experiment was conducted with two commercial maize cultivars (Zhengdan 958 and Denghai 605) using a lower level of N input (180 kg ha−1) by setting up single application at sowing and split application at sowing and later stages (V12, R1, and R2) with four different ratios, respectively. The maize yield with split-applied 180 kg ha−1 N did not decrease compared to the average yield with 240 kg ha−1 N input in farmer practice, while it increased by 6.7% to 11.5% in the four N split-application treatments compared with that of the single-application control. Morphological and physiological analyses demonstrated that late split application of N (i) increased the net photosynthetic rate and chlorophyll content and thus promoted the photosynthetic efficiency during the reproductive stages; (ii) promoted the sink capacity via improved kernel number, endosperm cells division, and grain-filling rate; and (iii) increased the final N content and N efficiency in the plant. Therefore, we propose that late split application of N could reduce N fertilizer input and coordinately improve N efficiency and grain yield in summer maize production, which are likely achieved by optimizing the source–sink relations during the grain-filling stage.